A review of recent progress in polymeric electrospun nanofiber membranes in addressing safe water global issues. Issue 16 (4th March 2021) - T. M., Subrahmanya; Arshad, Ahmad Bin; Lin, Po Ting; Widakdo, Januar; H. K., Makari; Austria, Hannah Faye M.; Hu, Chien-Chieh; Lai, Juin-Yih; Hung, Wei-Song
Abstract : This review provides an overview of recent advances and developments in electrospinning technology and the recent progress and applications of electrospun nanofiber membranes to expel various pollutants from water. Abstract : With rapid advancement in water filtration materials, several efforts have been made to fabricate electrospun nanofiber membranes (ENMs). ENMs play a crucial role in different areas of water treatment due to their several advantageous properties such as high specific surface area, high interconnected porosity, controllable thickness, mechanical robustness, and wettability. In the broad field of water purification, ENMs have shown tremendous potential in terms of permeability, rejection, energy efficiency, resistance to fouling, reusability and mechanical robustness as compared to the traditional phase inversion membranes. Upon various chemical and physical modifications of ENMs, they have exhibited great potential for emerging applications in environment, energy and health sectors. This review firstly presents an overview of the limiting factors influencing the morphology of electrospun nanofibers. Secondly, it presents recent advancements in electrospinning processes, which helps to not only overcome drawbacks associated with the conventional electrospinning but also to produce nanofibers of different morphology and orientation with an increased rate of production. Thirdly, it presents a brief discussion about the recent progress of the ENMs for removal of various pollutants from aqueous system through major areas of membrane separation. Finally, this review concludes with the challenges and future directions in this vast and fast growing area.